1970
DOI: 10.2134/agronj1970.00021962006200060014x
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Absorption and Distribution of 2,3,5‐Triiodobenzoic Acid (TIBA) in Soybeans (Glycine max)1

Abstract: The anticipated commercialization of TIBA as one of the first growth regulators for use on a major field crop in the USA, created a need for information on its absorption and movement in the soybean plant under field conditions. Such information would be of assistance in metabolite and residue studies. TIBA tagged with I‐131 was applied at early bloom in two field experiments and in a third study it was applied at the beginning of the pod filling stage of growth. Whole plants were sampled periodically, divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1972
1972
1991
1991

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
2
Order By: Relevance
“…In addition, it was shown that the uptake of [^"^CJ-NAA by mung bean segments was 6-fold greater in the presence of DTNB than in its absence (Arteca 1982a). Application of the auxin transport inhibitor 2,3,5triiodobenzoic acid (TIBA) has been shown to increase seed yield in sunflower, soybean, snapbean, bengalgram and redgram (Sant'Anna et al 1970, Spitznagle et al 1968), TIBA is known to prevent basipetal movement of auxin, and it has been suggested that basipetal movement of other growth regulators may also be inhibited by TIBA (Prasad and Krishna Sastry 1978). TIBA is regarded as a weak auxin antagonist in stem tissue, being able to suppress the activity of auxin at high concentrations while having no significant auxin activity itself (Katekar and Geissler 1980).…”
mentioning
confidence: 99%
“…In addition, it was shown that the uptake of [^"^CJ-NAA by mung bean segments was 6-fold greater in the presence of DTNB than in its absence (Arteca 1982a). Application of the auxin transport inhibitor 2,3,5triiodobenzoic acid (TIBA) has been shown to increase seed yield in sunflower, soybean, snapbean, bengalgram and redgram (Sant'Anna et al 1970, Spitznagle et al 1968), TIBA is known to prevent basipetal movement of auxin, and it has been suggested that basipetal movement of other growth regulators may also be inhibited by TIBA (Prasad and Krishna Sastry 1978). TIBA is regarded as a weak auxin antagonist in stem tissue, being able to suppress the activity of auxin at high concentrations while having no significant auxin activity itself (Katekar and Geissler 1980).…”
mentioning
confidence: 99%
“…In addition, plant heights were reduced and, petiole lengths of young leaves, shortened. From studies with foliar-applied TIBA labeled with 131 1, Sant' Anna et al (18) and Spitznagle et al (19) showed that radioactivity was readily translocated to other areas of the plant, primarily to meristems and young tissues. Krause and Boke (12) investigated the anatomical changes of the leaf structure resulting from foliar applied TIBA.…”
Section: Resultsmentioning
confidence: 99%
“…Estas alterações parecem ser o principal resultado de sua ação, variando em intensidade em função da idade da planta e entre cultivares de uma mesma espécie (SANTANNA et al, 1970), além da concentração utilizada. Kroll e Moore (1981), ao analisarem cortes transversais do caule de soja tratada com TIBA, constataram a ausência de elementos de vaso em um pequeno segmento anelar do córtex, formado logo após a aplicação do produto, relacionando esta alteração anatômica à redução da colonização da planta por Macrophomina phaseolina.…”
Section: Revisão Bibliográficaunclassified
“…Este mesmo autor obteve aumento de massa de grãos na ordem de 7,0% a 9,8% e redução da altura final entre 7,7% e 8,7%, quando o retardador foi aplicado entre os estádios vegetativos V5 e V7 (em variedade com hábito de crescimento determinado). Em espaçamento entre linhas reduzido, ocorreu aumento da massa de grãos em 6,5%, com redução de 18,0% na altura das plantas (WAX; PENDLETON, 1968 A translocação do TIBA na planta é realizada rapidamente, encontrando-se traços em raízes logo após a aplicação (SANTANNA et al, 1970), e em atividade nos meristemas laterais, folhas novas e locais de alta atividade de crescimento (OHKI;MCBRIDE, 1973). Segundo Santanna et al (1970) Segundo POTAFÓS (1994), em função da alta mobilidade do P nas plantas, sob condições de deficiência, há a translocação do nutriente das folhas mais velhas para as mais novas, esgotando sua reserva nas folhas mais velhas, onde o sintoma de deficiência aparece primeiro.…”
Section: Revisão Bibliográficaunclassified